Evaluation of Prescriptions and Types of Medication Prescribed by General Dental Practitioners in Qom, Iran, 2018-2019 - Mohammad Mehdizadeh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2020)
Background and Objectives: The rational prescription of the drug and consideration of its principles affect the treatment outcome. Regarding this, the purpose of this study was to evaluate prescriptions to check if they follow the given principles and investigate the prescribed medications by dentists.